A novel bacterial community index to assess stream ecological health. (6th July 2015) - Lau, Kelvin E. M.; Washington, Vidya J.; Fan, Vicky; Neale, Martin W.; Lear, Gavin; Curran, James; Lewis, Gillian D.
Summary In stream ecosystems, bacterial communities play an important role in nutrient and energy cycling processes as they are among the most numerous and active organisms at the basal trophic level of the stream food web. Bacterial communities in stream biofilms have been shown to correlate well with different catchment land use and therefore provide an opportunity for the development of a novel ecological indicator of stream ecosystem health. In this study, a bacterial community index (BCI) model was developed and validated using a national data set of biofilm bacterial community profiles collected from 223 streams across seven geographical regions in New Zealand. The six‐component BCI model was generated using the partial least squares regression method to associate the multivariate bacterial community profile with the macroinvertebrate community index, which is a well‐established indicator of stream health. Despite strong regional clustering of the bacterial community profiles, the BCI was indicative of the level of disturbance in the catchment, as shown by significant correlations with a wide range of independent indicators of water quality, macroinvertebrate community data, ecosystem functioning and catchment land‐use data. The BCI was able to explain 35% of the variation in a multi‐metric index incorporating ten common ecological parameters, suggesting that the stream bacterial communities could provide useful information about the ecosystem integrity. The BCI provides a novel ecosystem assessment tool, which can be used to complement existing stream health measures in the management of anthropogenic impacts on freshwater streams and rivers.